Evaluation of Learning Outcome: The Comparison Between the Education Unit Level Curriculum (KTSP) and the 2013 Curriculum - Ananda, Rusydi (SCAD Independent, 2021)
This study aimed to describe the comparative implementation of learning outcome evaluations applied at MTsN 1 Medan by using the 2013 KTSP and Curriculum 2013. The method used in this study was qualitative methodology. Data collection techniques consisted of observation, interviews, and documentation. The research findings indicated that the differences in the assessment of learning outcomes between the KTSP curriculum and 2013 curriculum include aspects of the application in the classroom, assessment aspects, aspects of the assessment system, aspects of assessment instruments, aspects of portfolio assessment concepts, aspects of report card format, aspects of value list format, aspects of competency achievement indicators, aspects of competency achievement indicators, aspects graduate competency standards, standard aspects of assessment and aspects of value ranges.